2023
DOI: 10.1186/s12964-023-01113-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation propensity of the intrinsically disordered AB region of human RXRβ

Abstract: RXRβ is one of three subtypes of human retinoid X receptor (RXR), a transcription factor that belongs to the nuclear receptor superfamily. Its expression can be detected in almost all tissues. In contrast to other subtypes – RXRα and RXRγ – RXRβ has the longest and unique N-terminal sequence called the AB region, which harbors a ligand-independent activation function. In contrast to the functional properties of this sequence, the molecular properties of the AB region of human RXRβ (AB_hRXRB) have not yet been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 101 publications
1
0
0
Order By: Relevance
“…We titrated PEG and found that 10% is sufficient for HP1α phase separation alone (Figure 3A). This percentage of PEG is similar to that used in previous studies (16, 17, 24-26). In the absence of PEG, HP1α alone does not phase separate at concentrations up to 800 µ M (8, 19).…”
Section: Resultssupporting
confidence: 86%
“…We titrated PEG and found that 10% is sufficient for HP1α phase separation alone (Figure 3A). This percentage of PEG is similar to that used in previous studies (16, 17, 24-26). In the absence of PEG, HP1α alone does not phase separate at concentrations up to 800 µ M (8, 19).…”
Section: Resultssupporting
confidence: 86%